2016
DOI: 10.1097/mcg.0000000000000606
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Dysfunction and Neuropathologic Correlations in Parkinson Disease

Abstract: Gastrointestinal disturbances are frequent in PD. ENS's synucleinopathy could entirely explain pathophysiology of digestive dysfunction and is correlated with severity of gastrointestinal symptoms in PD. Biopsies may show α-SYN aggregates in immunoreactive Lewy neurites in the submucosal and myenteric plexus. Thus, endoscopic and immunohistochemical exploration of ENS may be a biomarker for Parkinson enteropathy and for PD overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…[ 7 , 8 ] Increasing evidence indicates that PD is also involved in the dopamine system of other organs (such as pathways in the mesolimbic system, mesocortical pathways, and dopaminergic neurons in the gastrointestinal tract), the serotonergic system, cholinergic system, noradrenergic system, and peptide neurotransmitter systems (such as enkephalin system and dynorphin system), likely underlying a series of non-motor PD symptoms. [ 9 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 , 8 ] Increasing evidence indicates that PD is also involved in the dopamine system of other organs (such as pathways in the mesolimbic system, mesocortical pathways, and dopaminergic neurons in the gastrointestinal tract), the serotonergic system, cholinergic system, noradrenergic system, and peptide neurotransmitter systems (such as enkephalin system and dynorphin system), likely underlying a series of non-motor PD symptoms. [ 9 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Lewy type pathology also emerges in the peripheral autonomous nervous system (PANS) [1, 2] and is known to occur in early, prodromal stages. Abnormal aggregates of synuclein are not uncommon in the enteric neurons of PD patients and the evidence of a prion-like behavior of synuclein [3] has focused the attention on the assessment of the enteric nervous system in PD in line with the hypothesis that the gut is the initial site of synuclein aggregation [46]. Since abnormal aggregates of synuclein are found in the enteric neurons in PD, a colonic biopsy could provide access to a unique tissue to study pathophysiological aspects of the disease [46].…”
Section: Introductionmentioning
confidence: 99%
“…Although the main molecular features remaining at the core of PD etiopathogenesis are (i) mitochondrial alterations, (ii) oxidative damage, and (iii) the mishandling degradation of proteins [2123], only unfolded proteins have been assessed at PANS level [46] from subjects suffering from idiopathic REM sleep behavior disorder (iRBD), a parasomnia characterized by dream enactment behavior and atonia during REM sleep. iRBD patients are considered to suffer prodromal synucleinopathies since up to 80% of these patients develop a neurodegenerative disease, associated with Lewy body pathology [2426].…”
Section: Introductionmentioning
confidence: 99%
“…A53T alpha-synuclein mice developed age-related declines in stool frequency and gastric emptying consistent with those seen in human PD (Noorian et al, 2012 ). One clinical study reported that synucleinopathy in the enteric nervous system was significantly correlated with frequency and severity of GI dysfunction motor disability in PD patients (Mrabet et al, 2016 ), supporting the relationship between alpha-synuclein deposition in the enteric nervous system and GI dysfunction. In the present study, the GI dysfunctions are taken in account considering that the dietary iron supplements might induce and interact synucleinopathy on this primary site.…”
Section: Discussionmentioning
confidence: 91%